The Jossey-Bass reader on educational leadership - Grogan, Margaret (Jossey-Bass, 2013)
The newest edition of the bestselling book on educational leadership This expanded and thoroughly updated edition of the popular anthology contains the articles, book excerpts, and seminal reports that define and drive the field of educational leadership today.